Composite particle for positive electrode of electrochemical element, method for producing the same, positive electrode for electrochemical element, and electrochemical element
Patent Information
- Application Number
- CN202580020699.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-20
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to composite particles for the positive electrode of electrochemical devices and a method for manufacturing the same, as well as a positive electrode and an electrochemical device comprising the composite particles. Background Technology
[0002] Electrochemical components such as lithium-ion secondary batteries are used in a wide range of applications, requiring further improvements in their performance. In most cases, the positive electrode of an electrochemical component has a current collector and a positive electrode composite material layer disposed on its surface.
[0003] Traditionally, wet-process methods have been widely used to form the cathode composite material layer. The wet-process method refers to coating a slurry composition containing a cathode active material, a binder resin, and a solvent onto the surface of a current collector, and then drying the slurry composition to form the cathode composite material layer.
[0004] However, in recent years, dry-forming methods have attracted attention for more efficient positive electrode formation. In dry-forming methods, composite particles containing a positive electrode active material and a binding resin are prepared, and these composite particles are deposited on the surface of a current collector to form a layer of composite particles. This layer is then pressed to reduce its thickness, thereby forming a positive electrode composite material layer. Patent Document 1 describes a technique for composite particles used in this dry-forming method.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-78497 (corresponding publication: U.S. Patent Application Publication No. 2014 / 0079872) Summary of the Invention
[0008] The problem the invention aims to solve
[0009] From the viewpoint of reducing the internal resistance of electrochemical elements, composite particles with low powder resistance are preferred. This invention was made in view of such a problem, and its object is to provide a composite particle for the positive electrode of an electrochemical element with low powder resistance, a method for manufacturing the same, and a positive electrode and an electrochemical element comprising the composite particle.
[0010] Solution for solving the problem
[0011] The inventors conducted in-depth research with the aim of solving the above-mentioned problems. As a result, the inventors discovered that, in composite particles for the positive electrode of electrochemical elements comprising a positive electrode active material, a carbon-based conductive material, and a binding resin, composite particles for the positive electrode of electrochemical elements with a characteristic value representing the dispersion of carbon atoms within a specific range can have a small powder resistance, thereby completing the present invention.
[0012] That is, the present invention includes the following.
[0013] <1> A composite particle for the positive electrode of an electrochemical device comprises a positive electrode active material, a carbon-based conductive material, and a binding resin.
[0014] The carbon atom dispersion s in the composite particles for the positive electrode of the above-mentioned electrochemical element, calculated by the following formula (1), is... 2 It is between 0.5% and 1.0%.
[0015]
[0016] In equation (1), n represents the number of square images. The aforementioned square images are obtained by segmenting a 1280-pixel × 1024-pixel surface observation image obtained by taking a picture of the composite particles for the positive electrode of the aforementioned electrochemical element at a magnification of 2000 using a scanning electron microscope. The square images have a size of 100 pixels vertically × 100 pixels horizontally and do not include blank areas where the composite particles for the positive electrode of the aforementioned electrochemical element were not captured.
[0017] n is 80 or higher and 120 or lower
[0018] x i This indicates the area ratio of carbon atoms in each of the above images.
[0019] x a This represents the average area ratio of carbon atoms in all the above images.
[0020] <2> according to <1> The composite particles for the positive electrode of the electrochemical element have a particle strength of 0.6 or more. The particle strength is expressed as the ratio of the D50 particle size "D50(0.25MPa)" measured under a pressure of 0.25MPa to the D50 particle size "D50(0.1MPa)" measured under a pressure of 0.1MPa, which is "D50(0.25MPa) / D50(0.1MPa)".
[0021] <3> according to <1> or <2> The composite particles used for the positive electrode of the electrochemical element have an in-plane cross-sectional area of 3.1 cm². 24.0g of the above-mentioned composite particles for the positive electrode of the electrochemical element were placed in a container, and the powder resistance of the above-mentioned composite particles for the positive electrode of the electrochemical element was measured to be less than 30Ω under a pressure of 20kN.
[0022] <4> according to <1> ~ <3> The composite particles for the positive electrode of the electrochemical element according to any one of the following methods, wherein the content of the above-mentioned positive electrode active material is 90% by weight or more and 99.19% by weight or less.
[0023] <5> according to <1> ~ <4> The composite particles for the positive electrode of the electrochemical element according to any one of the following methods, wherein the content of the carbon-based conductive material is 0.8% by weight or more and 5% by weight or less.
[0024] <6> according to <1> ~ <5> The composite particles for the positive electrode of the electrochemical element according to any one of the following methods, wherein the content of the above-mentioned binding resin is 0.01% by weight or more and 5% by weight or less.
[0025] <7> according to <1> ~ <6> The composite particles for the positive electrode of the electrochemical element as described in any one of the above-mentioned carbon-based conductive materials have a D50 particle size of 0.01 μm to 0.4 μm.
[0026] <8> A method for manufacturing composite particles for the positive electrode of an electrochemical device involves manufacturing the aforementioned... <1> to <7> The method for manufacturing composite particles for the positive electrode of an electrochemical element according to any one of the following methods includes: stirring and granulating the positive electrode active material, the carbon-based conductive material, the binder resin, and the solvent.
[0027] <9> according to <8> The method for manufacturing composite particles for the positive electrode of the electrochemical element includes: step (i) of stirring the positive electrode active material in a granulation tank to obtain a stirred state; and
[0028] Step (ii) involves spraying a liquid composition comprising the carbon-based conductive material, the binder resin, and the solvent onto the above-mentioned positive electrode active material in a stirred state.
[0029] <10> according to <9> The method for manufacturing composite particles for the positive electrode of the electrochemical element, wherein the relative vapor pressure of the solvent in the granulation tank in step (ii) is 0.1 or more and 0.9 or less.
[0030] <11> according to <10> The method for manufacturing composite particles for the positive electrode of the electrochemical element, wherein step (ii) includes spraying the liquid composition from a nozzle disposed at the top of the granulation tank.
[0031] The relative vapor pressure of the solvent in the granulation tank in the above-mentioned process (ii) is 0.5 or higher.
[0032] <12> according to <10> The method for manufacturing composite particles for the positive electrode of the electrochemical element, wherein step (ii) includes spraying the liquid composition from a nozzle disposed on the side of the granulation tank.
[0033] The relative vapor pressure of the solvent in the granulation tank in the above-mentioned process (ii) is less than 0.3.
[0034] <13> A positive electrode for an electrochemical device has a current collector and a positive electrode composite material layer formed on the current collector.
[0035] The positive electrode composite material layer contains <1> ~ <7> The composite particles for the positive electrode of the electrochemical element as described in any one of the above.
[0036] <14> An electrochemical element having <13> The electrochemical element described herein uses a positive electrode.
[0037] Invention Effects
[0038] According to the present invention, it is possible to provide a composite particle for an electrochemical element cathode with low powder resistance and a method for manufacturing the same, as well as an electrochemical element cathode and an electrochemical element comprising the composite particle. Attached Figure Description
[0039] Figure 1 This is a top view schematically illustrating a granulation tank used in a method for manufacturing composite particles according to one embodiment of the present invention.
[0040] Figure 2 This is a schematic cross-sectional view of a granulation tank used in a method for manufacturing composite particles according to one embodiment of the present invention.
[0041] Figure 3 This is a graph showing the relationship between the dispersion and powder resistance of embodiments and comparative examples of the present invention. Detailed Implementation
[0042] The present invention will now be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples described below, and may be implemented in any manner without departing from the scope of the claims and their equivalents.
[0043] Unless otherwise specified, in polymers made by copolymerizing multiple monomers, the proportion of monomer units formed by polymerizing a particular monomer in the polymer is usually consistent with the proportion (feed ratio) of that particular monomer in all the monomers used in the polymerization of the polymer.
[0044] The structure of structural units, molecules, or parts thereof is not limited by their manufacturing method. For example, an aromatic vinyl monomer unit is a structural unit having a structure formed by the polymerization of aromatic vinyl monomers, but this aromatic vinyl monomer unit also includes units having the same structure as those formed by the polymerization of aromatic vinyl monomers, formed by other forming methods. Furthermore, for example, a conjugated diene monomer unit is a structural unit having a structure formed by the polymerization of conjugated diene monomers, but this conjugated diene monomer unit also includes units having the same structure as those formed by the polymerization of conjugated diene monomers, formed by other forming methods.
[0045] In the following description, unless otherwise stated, the orientation of elements as “parallel,” “perpendicular,” and “orthogonal” may also include errors within, for example, the range of ±3°, ±2°, or ±1°, without impairing the effects of the invention.
[0046] In the following description, unless otherwise stated, the term "(meth)acrylic acid" includes acrylic acid, methacrylic acid, and mixtures thereof.
[0047] <Overview of Composite Particles>
[0048] A composite particle (hereinafter, sometimes referred to as "composite particle") for the positive electrode of an electrochemical device according to one embodiment of the present invention comprises a positive electrode active material, a carbon-based conductive material, and a binding resin. Typically, one or more positive electrode active material particles and one or more carbon-based conductive material particles are bonded together with a binding resin to form a composite particle. This composite particle can be used as a powdered material for forming the positive electrode of an electrochemical device.
[0049] The composite particles of this embodiment have a specific range of carbon atom dispersion s 2 Here, the dispersion of carbon atoms is s. 2 The characteristic value calculated by equation (1) represents the degree of dispersion of the carbon atoms in the composite particles. The carbon atoms include both the carbon atoms contained in the carbon-based conductive material and the carbon atoms that can be contained in the adhesive resin.
[0050]
[0051] In equation (1), n represents the number of square images. The aforementioned square images are obtained by segmenting a 1280-pixel × 1024-pixel surface observation image of the composite particles obtained by photographing them at 2000x magnification using a scanning electron microscope. The square images have a size of 100 pixels vertically × 100 pixels horizontally and do not include blank areas where the composite particles were not photographed.
[0052] n is 80 or higher and 120 or lower
[0053] x i This indicates the area ratio of the carbon atoms captured in each of the above images.
[0054] x a This represents the average area ratio of the carbon atoms captured in all the above images.
[0055] The composite particles of this embodiment exhibit low powder resistivity. This reduces the resistance of the positive electrode (hereinafter, sometimes simply referred to as "positive electrode") used in electrochemical devices manufactured using these composite particles, thereby lowering the internal resistance of the electrochemical device. Furthermore, the composite particles of this embodiment typically possess high particle strength. This suppresses particle damage even when the positive electrode active material particles expand and contract due to charging and discharging, reducing the disruption of conductive pathways caused by particle damage and thus improving the cycle characteristics of the electrochemical device.
[0056] <Dispersion of carbon atoms>
[0057] The carbon atom dispersion s in the composite particles of this embodiment 2 The range is typically 0.5% or more, more preferably 0.6% or more, further preferably 0.7% or more, even more preferably 0.8% or more, and still even more preferably 0.81% or more. The upper limit is typically 1.0% or less, preferably 0.9% or less, more preferably 0.89% or less, and even more preferably 0.82% or less. Therefore, the dispersion s of carbon atoms... 2 The range can be, for example, 0.5% or higher and 1.0% or lower, 0.5% or higher and 0.9% or lower, 0.5% or higher and 0.89% or lower, 0.5% or higher and 0.82% or lower, 0.6% or higher and 1.0% or lower, 0.6% or higher and 0.9% or lower, 0.6% or higher and 0.89% or lower, 0.6% or higher and 0.82% or lower, 0.7% or higher and 1.0% or lower, and 0.7% or higher and 0.9% or lower. The ranges are: 0.7% to 0.89%, 0.7% to 0.82%, 0.8% to 1.0%, 0.8% to 0.9%, 0.8% to 0.89%, 0.8% to 0.82%, 0.81% to 1.0%, 0.81% to 0.9%, 0.81% to 0.89%, or 0.81% to 0.82%. This applies to the dispersion of carbon atoms (s). 2Within the aforementioned range, the powder resistance of the composite particles can be reduced, and the particle strength of the composite particles can usually be increased.
[0058] Dispersion of carbon atoms s 2 The characteristic value is calculated using equation (1) above. The dispersion s of this carbon atom is... 2 It is possible to obtain n square images of the composite particle at 2000x magnification using a scanning electron microscope, and to calculate based on these images using Equation (1). Specifically, the composite particle is photographed at 2000x magnification to obtain a surface observation image of 1280 pixels × 1024 pixels. This surface observation image is divided into square images of 100 pixels vertically × 100 pixels horizontally. From the multiple square images thus obtained, n images that do not contain blank areas are selected. The term "blank area" refers to the portion where the composite particle was not photographed. In each of these n images, the area ratio x of carbon atoms relative to the area of 100% of the image is calculated. i (i represents an integer from 1 to n). Furthermore, calculate the area ratio x of carbon atoms for all n images. i average x a Then, for the area ratio x of all n carbon atoms... i With average x a The square of the difference (x) i -x a ) 2 Summing the values and dividing the sum by the number of images, n, allows us to calculate the dispersion s of carbon atoms in the composite particles. 2 The number of images, n, is typically 80 or more, preferably 90 or more, and more preferably an integer greater than 95. The upper limit for the number n is typically 120 or less, but can also be 100 or less. In one example, the number of images, n, can be in the range of 80 or more but less than 120.
[0059] The area ratio x of carbon atoms in each of the above n squares iCalculations can be performed through image analysis. Image analysis can be performed using the image processing software "OpenCV" (https: / / opencv.org / ). For example, if an image contains three parts: the positive electrode active material, the carbon atom part, and the void part, ternary processing can be used to separate these parts, thereby calculating the area ratio of the carbon atom part. Typically, since each part has a different brightness value, the above ternary processing can be performed based on the brightness value of the pixels. In a specific example, if the positive electrode active material is captured as the high-brightness part, the void as the low-brightness part, and the carbon atom as the intermediate-brightness part, the brightness value of the pixel with the highest brightness value in the image is set to "100", the brightness value of the pixel with the lowest brightness value in the image is set to "0", and a first threshold (e.g., 30) is set to distinguish between voids and carbon atoms, and a second threshold (e.g., 70) is set to distinguish between carbon atoms and positive electrode active material. Then, using these first and second thresholds for ternaryization, the area ratio of carbon atoms can be calculated based on the area of carbon atoms represented by pixels with brightness values between the first and second thresholds. The dispersion s of carbon atoms 2 The measurement can also be performed using the methods described in the embodiments described later.
[0060] Dispersion of carbon atoms s 2 For example, in a method for manufacturing composite particles produced by stirred granulation using a granulation tank, the relative vapor pressure of the solvent within the granulation tank can be adjusted. This relative vapor pressure indicates the degree of humidity of the environment within the granulation tank due to the solvent. Generally, there is a tendency for lower relative vapor pressure to result in higher dispersion, and higher relative vapor pressure to result in lower dispersion. Therefore, by appropriately setting the relative vapor pressure within the granulation tank according to the composition of the raw materials for the composite particles, a carbon atom dispersion s within the aforementioned specific range can be obtained. 2 .
[0061] <Positive Electrode Active Material>
[0062] A positive electrode active material is a substance that facilitates electron transfer at the positive electrode of an electrochemical element. For example, as a positive electrode active material for lithium-ion secondary batteries, a substance capable of absorbing and releasing lithium is typically used. Inorganic compounds are preferred as this positive electrode active material. Examples of inorganic compounds suitable for use as positive electrode active materials include transition metal oxides, transition metal sulfides, and lithium-containing composite metal oxides containing lithium and transition metals. Examples of transition metals include, for instance, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo.
[0063] Examples of transition metal oxides include MnO, MnO2, V2O5, and V6O. 13 The preferred materials include TiO2, Cu2V2O3, amorphous V2O-P2O5, and MoO3. From the perspective of cycle stability and capacity, MnO, V2O5, and V6O are preferred. 13 And TiO2.
[0064] Examples of transition metal sulfides include TiS2, TiS3, amorphous MoS2, and FeS.
[0065] Examples of lithium-containing composite metal oxides include those with layered structures, spinel structures, and olivine-type structures. Examples of lithium-containing composite metal oxides with layered structures include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Co-Ni-Mn lithium composite oxides, Ni-Mn-Al lithium composite oxides, and Ni-Co-Al lithium composite oxides. Examples of lithium-containing composite metal oxides with spinel structures include lithium manganese oxide (LiMn2O4) and Li[Mn2O4], which is formed by replacing a portion of Mn with other transition metals. 3 / 2 M 1 1 / 2 ]O4(Here, M 1 This refers to transition metals other than Mn, such as Cr, Fe, Co, Ni, and Cu. Examples of lithium-containing composite metal oxides with an olivine-type structure include, for instance, Li. X M 2 PO4 (where M is in the formula) 2 The symbol represents at least one element selected from Mn, Fe, Co, Ni, Cu, Mg, Zn, V, Ca, Sr, Ba, Ti, Al, Si, B, and Mo, where X represents a number satisfying 0 ≤ X ≤ 2. The symbol represents an olivine-type lithium phosphate compound. A single positive electrode active material can be used alone, or two or more can be used in combination.
[0066] The positive electrode active material typically has a particulate shape. The D50 particle size of the positive electrode active material is preferably 0.03 μm or more, more preferably 0.1 μm or more, even more preferably 1.0 μm or more, and preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 30 μm or less. When the D50 particle size of the positive electrode active material is within the above range, the powder resistivity of the composite particles can be effectively reduced, and the particle strength of the composite particles can generally be effectively improved.
[0067] The D50 of the positive electrode active material can be measured using the following method. With the positive electrode active material dispersed using an airflow at a dispersion pressure of 0.25 MPa, a laser diffraction particle size distribution measuring device is used to measure the particle size distribution of the positive electrode active material on a volume basis. From the obtained particle size distribution, the particle size that accounts for 50% of the cumulative volume from the smallest diameter side (the median particle size D50) can be used as the D50 particle size of the positive electrode active material.
[0068] The content of the positive electrode active material relative to 100% by weight of the composite particles is preferably 90% by weight or more, more preferably 93% by weight or more, even more preferably 95% by weight or more, and preferably 99.19% by weight or less, more preferably 99% by weight or less, and even more preferably 98% by weight or less. Therefore, the range of the content of the positive electrode active material relative to 100% by weight of the composite particles can be, for example, 90% by weight or more and 99.19% by weight, 90% by weight or more and 99% by weight, 90% by weight or more and 98% by weight, 93% by weight or more and 99.19% by weight, 93% by weight or more and 99% by weight, 93% by weight or more and 98% by weight, 95% by weight or more and 99.19% by weight, 95% by weight or more and 99% by weight, or 95% by weight or more and 98% by weight. When the content of positive electrode active material is within the above range, the powder resistance of composite particles can be effectively reduced, and the particle strength of composite particles can usually be effectively improved.
[0069] <Carbon-based conductive materials>
[0070] Carbon-based conductive materials are carbon materials that form conductive pathways between positive electrode active materials. Examples of carbon-based conductive materials include, for instance, carbon black (e.g., acetylene black, Ketjen black, furnace black, etc.); single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include stacked cup types); carbon nanotubes; vapor-grown carbon fibers; milled carbon fibers obtained by pulverizing polymer fibers after sintering; single-layer or multi-layer graphene; carbon nonwoven fabric sheets obtained by sintering nonwoven fabrics made of polymer fibers; and other conductive carbon materials. Carbon black is preferred. One type of carbon-based conductive material can be used alone, or two or more can be used in combination.
[0071] There are no particular restrictions on the shape of carbon-based conductive materials; they can be, for example, granular, fibrous, or foil-like.
[0072] The D50 particle size range of the carbon-based conductive material in the composite particles is preferably 0.01 μm or more, more preferably 0.02 μm or more, even more preferably 0.05 μm or more, and preferably 0.4 μm or less, more preferably 0.2 μm or less, and even more preferably 0.15 μm or less. Therefore, the D50 particle size range of the carbon-based conductive material can be, for example, a range of 0.01 μm or more and 0.4 μm or less, a range of 0.01 μm or more and 0.2 μm or less, a range of 0.01 μm or more and 0.15 μm or less, a range of 0.02 μm or more and 0.4 μm or less, a range of 0.02 μm or more and 0.2 μm or less, a range of 0.02 μm or more and 0.15 μm or less, a range of 0.05 μm or more and 0.4 μm or less, a range of 0.05 μm or more and 0.2 μm or less, or a range of 0.05 μm or more and 0.15 μm or less. When the D50 particle size of carbon-based conductive materials is within the above range, the powder resistance of composite particles can be effectively reduced, and the particle strength of composite particles can usually be effectively improved.
[0073] The D50 particle size of carbon-based conductive materials can be measured using the following method. With the carbon-based conductive material dispersed using an airflow at a dispersion pressure of 0.25 MPa, the particle size distribution of the carbon-based conductive material is measured using a laser diffraction particle size distribution measuring device, with volume as the reference. From the obtained particle size distribution, the particle size that accounts for 50% of the cumulative volume from the smallest diameter side (the median particle size D50) can be used as the D50 particle size of the carbon-based conductive material.
[0074] The content of carbon-based conductive material relative to 100% by weight of composite particles is preferably 0.8% by weight or more, more preferably 1.0% by weight or more, even more preferably 1.5% by weight or more, and preferably 5% by weight or less, more preferably 4% by weight or less, and even more preferably 3% by weight or less. Therefore, the range of the content of carbon-based conductive material relative to 100% by weight of composite particles can be, for example, 0.8% by weight or more and 5% by weight, 0.8% by weight or more and 4% by weight, 0.8% by weight or more and 3% by weight, 1.0% by weight or more and 5% by weight, 1.0% by weight or more and 4% by weight, 1.0% by weight or more and 3% by weight, 1.5% by weight or more and 5% by weight, 1.5% by weight or more and 4% by weight, or 1.5% by weight or more and 3% by weight. When the content of carbon-based conductive material is within the above range, the powder resistance of the composite particles can be effectively reduced, and the particle strength of the composite particles can generally be effectively improved.
[0075] <Adhesive Resin>
[0076] A binder resin is a resin used to bond positive electrode active materials and carbon-based conductive materials. Polymers are typically used as binder resins. Examples of polymers that can be used as binder resins include conjugated diene polymers, acrylic polymers, aromatic vinyl block polymers, fluorinated polymers, cellulose polymers, and cyclic olefin polymers.
[0077] Conjugated diene polymers refer to polymers containing conjugated diene monomer units. Examples of conjugated diene monomers include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, 2-chloro-1,3-butadiene (chloroprene), and isoprene. Specific examples of conjugated diene polymers include styrene-butadiene copolymers (SBR), copolymers containing aromatic vinyl monomer units and aliphatic conjugated diene monomer units; butadiene rubber (BR); acrylonitrile-butadiene rubber (NBR) (a copolymer containing acrylonitrile and butadiene units); and their hydrides.
[0078] Examples of acrylic polymers include polymers containing crosslinking monomer units, (meth)acrylate monomer units, and monomer units containing acidic groups. The proportion of (meth)acrylate monomer units in the acrylic polymer is preferably 50% by weight or more, more preferably 55% by weight or more, even more preferably 58% by weight or more, and preferably 98% by weight or less, more preferably 97% by weight or less, and even more preferably 96% by weight or less.
[0079] Examples of aromatic vinyl block polymers include block polymers containing block regions composed of aromatic vinyl monomer units. Examples of aromatic vinyl monomers include styrene, styrene sulfonic acid and its salts, α-methylstyrene, p-tert-butylstyrene, butoxystyrene, vinyltoluene, chlorostyrene, and vinylnaphthalene, with styrene being preferred. Examples of aromatic vinyl block polymers include styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene copolymers, and their hydrides.
[0080] Fluoropolymers are polymers that contain fluorinated monomer units and may also contain non-fluorinated monomer units. Examples of fluorinated monomers include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, fluorinated vinylidene, trifluoroethylene, chlorotrifluoroethylene, 2,3,3,3-tetrafluoropropylene, and perfluoroalkyl vinyl ethers. Examples of fluorinated polymers include polytetrafluoroethylene, polychlorotrifluoroethylene, polyvinylidene fluoride, polyfluorinated vinylidene, perfluoroalkoxy fluoropolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene copolymers, ethylene-chlorotrifluoroethylene copolymers, and vinylidene fluoride-hexafluoropropylene copolymers (vinylidene fluoride-hexafluoropropylene copolymers).
[0081] Examples of cellulose-based polymers include cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose.
[0082] Examples of cyclic olefin polymers include polymers (addition polymers or ring-opening polymers) formed by the polymerization of cyclic olefin compounds and their hydrides, as well as hydrides of polymers formed by the polymerization of aromatic vinyl compounds. Since the swelling degree of the electrolyte and the glass transition temperature can be easily adjusted to suitable values, hydrides of ring-opening polymers formed by the ring-opening polymerization of cyclic olefin compounds and hydrides of polymers formed by the polymerization of aromatic vinyl compounds are preferred.
[0083] Examples of cyclic olefin compounds include unsubstituted or alkyl-containing norbornene such as norbornene, 5-methyl norbornene, 5-ethyl norbornene, 5-butyl norbornene, 5-hexyl norbornene, 5-decyl norbornene, 5-cyclohexyl norbornene, and 5-cyclopentyl norbornene; alkenyl-containing norbornene such as 5-ethylidene, 5-vinyl norbornene, 5-propenyl norbornene, 5-cyclohexenyl norbornene, and 5-cyclopentenyl norbornene; aromatic norbornene such as 5-phenyl norbornene; and 5-methoxycarbonyl norbornene, 5-ethoxycarbonyl norbornene, 5-methyl- 5-Methoxycarbonylnorbornene, 5-methyl-5-ethoxycarbonylnorbornene, norbornenyl-2-methylpropionate, norbornenyl-2-methyloctanoate, 5-hydroxymethylnorbornene, 5,6-di(hydroxymethyl)norbornene, 5,5-di(hydroxymethyl)norbornene, 5-hydroxy-isopropylnorbornene, 5,6-dicarboxylated norbornene, and 5-methoxycarbonyl-6-carboxylated norbornene are norbornenes containing polar groups including oxygen atoms; 5-cyanonorbornene and other norbornenes containing polar groups including nitrogen atoms; dicyclopentadiene, methyldicyclopentadiene, tricyclo[5.2.1.0] 2,6[Dec-8-ene and other polycyclic norbornene derivatives with three or more rings that do not contain aromatic rings; tetracyclic [9.2.1.0] 2,10 .0 3,8 [Tetradecano-3,5,7,12-tetraene (also known as 1,4-methylbridged-1,4,4a,9a-tetrahydro-9H-fluorene), tetracyclic [10.2.1.0] 2,11 .0 4,9 [Pentadecyl-4,6,8,13-tetraene (also known as 1,4-methylbridged-1,4,4a,9,9a,10-hexahydroanthracene) and other polycyclic norbornene compounds with aromatic rings of three or more rings; tetracyclic dodecene, 8-methyltetracyclic dodecene, 8-ethyltetracyclic dodecene, 8-cyclohexyltetracyclic dodecene, 8-cyclopentyltetracyclic dodecene, 8-methoxycarbonyl-8-methyltetracyclic [4.4.0.1] 2,5 .1 7,10 Unsubstituted or alkyl-containing tetracyclic dodecenes such as 3-dodecene; tetracyclic dodecenes with exocyclic double bonds such as 8-methylene tetracyclic dodecene, 8-ethylene tetracyclic dodecene, 8-vinyl tetracyclic dodecene, 8-propenyl tetracyclic dodecene, 8-cyclohexenyl tetracyclic dodecene, and 8-cyclopentenyl tetracyclic dodecene; tetracyclic dodecenes with aromatic rings such as 8-phenyl tetracyclic dodecene; 8-methoxycarbonyl tetracyclic dodecene, 8-methyl-8-methoxycarbonyl tetracyclic dodecene, 8-hydroxymethyl tetracyclic dodecene, 8-carboxylated tetracyclic dodecene, and tetracyclic dodecene. Tetracyclic dodecenes such as cyclododecene-8,9-dicarboxylic acid and tetracyclic dodecene-8,9-dicarboxylic anhydride have substituents containing oxygen atoms; tetracyclic dodecenes such as 8-cyanotetracyclic dodecene and tetracyclic dodecene-8,9-dicarboxyimide have substituents containing nitrogen atoms; tetracyclic dodecenes such as 8-chlorotetracyclic dodecene have substituents containing halogen atoms; tetracyclic dodecenes such as 8-trimethoxysilyltetracyclic dodecene have substituents containing silicon atoms; and hexacyclic heptadecenes such as the Diels-Alder additions of the above tetracyclic dodecenes and cyclopentadiene.
[0084] Among them, nonpolar norbornene monomers are preferred as cyclic olefin compounds; more preferably are unsubstituted or alkyl norbornene derivatives (e.g., norbornene, 8-ethyltetracyclododecene), alkenyl norbornene derivatives (e.g., ethylenetetracyclododecene (8-ethylenetetracyclododecene)), dicyclopentadiene, and norbornene derivatives with aromatic rings (e.g., tetracyclo[9.2.1.0]). 2,10 .0 3,8[Tetradecane-3,5,7,12-tetraene (also known as 1,4-methylbridged-1,4,4a,9a-tetrahydro-9H-fluorene)), unsubstituted or alkyl-containing tetracyclic dodecenes (e.g., tetracyclic dodecene, 8-methoxycarbonyl-8-methyltetracyclo[4.4.0.1]). 2,5 .1 7,10 ]-3-dodecene).
[0085] Polymers of cyclic olefin compounds capable of arbitrary hydrogenation can be polymers using only cyclic olefin compounds as monomers, or polymers using cyclic olefin compounds as monomers and any compound other than cyclic olefin compounds that can copolymerize. Polymers using only cyclic olefin compounds as monomers are preferred.
[0086] Polymers of cyclic olefin compounds capable of arbitrary hydrogenation, preferably polymers using tetracyclododecene, dicyclopentadiene, and norbornene as monomers, and more preferably ring-opening polymers using tetracyclododecene, dicyclopentadiene, and norbornene as monomers.
[0087] In the above polymers, copolymers comprising aromatic vinyl monomer units and conjugated diene monomer units, and their hydrogenated derivatives, are preferred; block copolymers comprising aromatic vinyl monomer blocks and conjugated diene monomer blocks, and their hydrogenated derivatives, are more preferred; and hydrogenated derivatives of block copolymers comprising aromatic vinyl monomer blocks and conjugated diene monomer blocks are particularly preferred. An aromatic vinyl monomer block is a block region comprising aromatic vinyl monomer units, or it may comprise only aromatic vinyl monomer units. Similarly, a conjugated diene monomer block is a block region comprising conjugated diene monomer units, or it may comprise only conjugated diene monomer units.
[0088] Aromatic vinyl monomer units represent structural units having a structure formed by polymerizing aromatic vinyl monomers. There may be one type of aromatic vinyl monomer unit or two or more types. The content of aromatic vinyl monomer units relative to all structural units contained in a total of 100% by weight of the copolymer is preferably 5% by weight or more, more preferably 10% by weight or more, further preferably 20% by weight or more, and preferably 50% by weight or less, more preferably 40% by weight or less, and further preferably 30% by weight or less.
[0089] A conjugated diene monomer unit represents a structural unit having a structure formed by polymerizing conjugated diene monomers. The type of conjugated diene monomer unit can be one or more. The content of conjugated diene monomer units relative to all structural units contained in a total of 100% by weight of the copolymer is preferably 50% by weight or more, more preferably 60% by weight or more, further preferably 70% by weight or more, and preferably 95% by weight or less, more preferably 90% by weight or less, and further preferably 80% by weight or less.
[0090] When the above copolymer is a block copolymer, its block structure can be, for example, a diblock structure having aromatic vinyl monomer blocks and conjugated diene monomer blocks; a triblock structure having aromatic vinyl monomer blocks, conjugated diene monomer blocks, and aromatic vinyl monomer blocks; or a pentablock structure having aromatic vinyl monomer blocks, conjugated diene monomer blocks, aromatic vinyl monomer blocks, conjugated diene monomer blocks, and aromatic vinyl monomer blocks.
[0091] The hydrogenation rate of the copolymer's hydride is not particularly limited, but is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more. The hydrogenation rate can be determined by... 1 Measurements were performed using H-NMR.
[0092] The bonding resin can be used alone or in combination with two or more.
[0093] The content of binder resin relative to 100% by weight of composite particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, further preferably 0.3% by weight or more, and preferably 5% by weight or less, more preferably 3% by weight or less, and further preferably 1% by weight or less. Therefore, the range of binder resin content relative to 100% by weight of composite particles can be, for example, 0.01% by weight or more and 5% by weight, 0.01% by weight or more and 3% by weight, 0.01% by weight or more and 1% by weight, 0.1% by weight or more and 5% by weight, 0.1% by weight or more and 3% by weight, 0.1% by weight or more and 1% by weight, 0.3% by weight or more and 5% by weight, 0.3% by weight or more and 3% by weight, or 0.3% by weight or more and 1% by weight. When the binder resin content is within the above ranges, the powder resistivity of the composite particles can be effectively reduced, and the particle strength of the composite particles can generally be effectively improved.
[0094] <Any ingredient>
[0095] The composite particles of this embodiment may further include any components and be combined with the aforementioned positive electrode active material, carbon-based conductive material, and binder resin. Examples of these arbitrary components include antioxidants such as phenolic antioxidants; reinforcing materials; leveling agents; viscosity modifiers; electrolyte additives, and other additives. Any additive may be used alone or in any combination of two or more in any proportion.
[0096] Furthermore, the composite particles may contain a solvent and be combined with the aforementioned positive electrode active material, carbon-based conductive material, binder, and any additives, etc., as solid components. The solvent may be a residue of the solvent used in the manufacturing method of the composite particles. The amount of solvent relative to 100% by weight of the composite particles is preferably 0% to 10% by weight, more preferably 0% to 5% by weight, further preferably 0% to 3% by weight, even more preferably 0% to 1% by weight, and still more preferably 0% to 0.5% by weight, or may be 0% by weight.
[0097] <Characteristics of Composite Particles>
[0098] The composite particles of this embodiment can have low powder resistance. Therefore, by using these composite particles, a positive electrode with low resistance can be manufactured, and thus, electrochemical components such as lithium-ion secondary batteries with low internal resistance can be obtained.
[0099] In one example, the cross-sectional area is 3.1 cm². 2 4.0g of composite particles are placed into a container and pressurized with 20kN. This forms a sample powder layer with the same cross-sectional area as the container. The resistance of this sample powder layer can then be measured as the powder resistance of the composite particles. The measured powder resistance of the composite particles is preferably 30Ω or less, more preferably 25Ω or less, and even more preferably 20Ω or less. A lower limit is more preferred, and values such as 1Ω or more, 5Ω or more, and 10Ω or more are possible. The aforementioned powder resistance can be measured, for example, by placing 4g of composite particles into a probe unit with the aforementioned cross-sectional area of a powder resistance measurement system (Mitsubishi Chemical Analysis Technology Co., Ltd. "MCP-PD51") and measuring it under a load of 20kN. Specific measurements can also be performed using the methods described in the examples described later.
[0100] The composite particles in this embodiment preferably have high particle strength. Composite particles with such high particle strength can suppress damage under stress. Typically, stress can be applied to composite particles because the particles of the positive electrode active material expand and contract during charging and discharging. In contrast, composite particles with high particle strength can suppress damage even under such stress, thus reducing the disruption of conductive paths due to charging and discharging. Therefore, electrochemical devices such as lithium-ion secondary batteries with minimal capacity reduction due to charging and discharging can be obtained. Specifically, the particle strength of the composite particles is preferably 0.60 or more, more preferably 0.65 or more, further preferably 0.70 or more, particularly preferably 0.75 or more, and typically 1.0 or less.
[0101] The particle strength of the composite particles is expressed as the ratio "D50(0.25MPa) / D50(0.1MPa)" of the composite particle's D50 particle size measured under a relatively high pressure of 0.25MPa to that measured under a relatively low pressure of 0.1MPa. Generally, when pressure is applied to particles, they may break down, resulting in a smaller particle size. The higher the mechanical strength of the particles, the more this breakdown is suppressed. Therefore, higher particle strength indicates greater resistance to pressure-induced breakage, and thus higher mechanical strength. The D50 particle size of the composite particles can be measured by laser diffraction, using a volume-based particle size distribution of the composite particles dispersed by airflows at dispersion pressures of 0.1MPa and 0.25MPa, and is taken as the particle size at which the cumulative volume reaches 50% from the smallest diameter side. This measurement can be performed, for example, using a laser diffraction particle size distribution measurement device (MICRO TRACK "MT-3000II"). Specific measurements can also be performed using the methods described in the embodiments described later.
[0102] There is no particular limitation on the D50 particle size "D50 (0.1 MPa)" of the composite particles. In one example, the D50 particle size "D50 (0.1 MPa)" of the composite particles is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 40 μm or more, and preferably 400 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less.
[0103] <Manufacturing Method of Composite Particles>
[0104] The composite particles of this embodiment can be manufactured by a manufacturing method including stirring and granulating a positive electrode active material, a carbon-based conductive material, a binder resin, and a solvent. In stirring and granulating, particles containing the solid components of the composition are produced by stirring the composition in a granulation tank. At this time, the composition can be supplied to the granulation tank in a single batch, or it can be continuously or intermittently fed into the composition. In addition, as needed, any additives other than the positive electrode active material, the carbon-based conductive material, the binder resin, and the solvent can be used in the stirring and granulating process.
[0105] Preferably, the method for manufacturing composite particles includes:
[0106] Step (i) involves stirring the positive electrode active material in a granulation tank to achieve a stirred state; and
[0107] Step (ii) involves spraying a liquid composition comprising a carbon-based conductive material, a binding resin, and a solvent onto a stirred positive electrode active material.
[0108] In this manufacturing method, a powder layer comprising the positive electrode active material, a carbon-based conductive material, and a binder resin is formed by spraying a liquid composition onto a stirred positive electrode active material. The powder layer may further contain a solvent and any additives. Within this powder layer, while receiving the carbon-based conductive material and binder resin through the spraying of the liquid composition, particle formation and granulation are performed by stirring, thereby manufacturing the aforementioned composite particles.
[0109] The liquid composition comprises a carbon-based conductive material, a binder resin, and a solvent. Furthermore, the liquid composition may further comprise any additives. In the liquid composition, the binder resin and any additives may be soluble in the solvent or dispersed without dissolving. On the other hand, it is preferable that the carbon-based conductive material is dispersed without dissolving in the solvent.
[0110] When a carbon-based conductive material is dispersed in a solvent in a liquid composition, the carbon-based conductive material preferably has a specific range of D50 particle size. Specifically, the D50 particle size range of the carbon-based conductive material in the liquid composition can be the same as the D50 particle size range of the carbon-based conductive material in the composite particles.
[0111] The D50 particle size of the carbon-based conductive material in the liquid composition can be measured by the following method. Using a laser diffraction particle size distribution measuring device, the particle size distribution of the carbon-based conductive material in the liquid composition is measured on a volume basis. From the obtained particle size distribution, the particle size that accounts for 50% of the cumulative volume from the smallest diameter side (the median particle size D50) can be determined as the D50 particle size of the carbon-based conductive material in the liquid composition.
[0112] As a solvent, a liquid capable of dissolving or dispersing carbon-based conductive materials and binding resins can be used. Examples of such solvents include water, and organic solvents can also be used. Examples of organic solvents include N-methyl-2-pyrrolidone, cyclohexane, n-hexane, acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, dichloromethane, and chloroform. Among these, organic solvents are preferred, more preferably organic solvents with a boiling point of 95°C or less at 1 atm, even more preferably organic solvents with a boiling point of 90°C or less at 1 atm, and particularly preferably organic solvents with a boiling point of 85°C or less at 1 atm. The lower limit of the boiling point of the organic solvent at 1 atm is preferably 50°C or more. Examples of preferred solvents having this boiling point include cyclohexane, n-hexane, acetone, methyl ethyl ketone, ethyl acetate, tetrahydrofuran, dichloromethane, and chloroform, with cyclohexane being particularly preferred. A single solvent can be used, or two or more solvents can be used in combination.
[0113] The amount of solvent is preferably selected in such a way that the concentration of the solid component in the liquid composition is within a specific range. Specifically, the concentration of the solid component in the liquid composition is preferably 1% by weight or more, more preferably 2% by weight or more, even more preferably 3% by weight or more, and preferably 40% by weight or less, more preferably 20% by weight or less, and even more preferably 15% by weight or less.
[0114] The liquid composition preferably has a viscosity within a specific range at 25°C. Specifically, the viscosity range of the liquid composition at 25°C is preferably 100 mPa or more, more preferably 150 mPa or more, even more preferably 200 mPa or more, and preferably 800 mPa or less, more preferably 600 mPa or less, and even more preferably 400 mPa or less. The viscosity of the liquid composition can be measured using a Type B viscometer (Toki Sangyo Co., Ltd. "TVB-10M") under measurement conditions of 25°C and 60 rpm. The rotor used during measurement is appropriately selected based on the viscosity.
[0115] Granulation tanks used in stirred granulation typically have stirring blades for stirring. These stirring blades are positioned at the lower vertical part of the granulation tank, allowing them to rotate about a rotation axis parallel to the vertical direction. Hereinafter, this stirring blade is sometimes referred to as the "main stirring blade." Furthermore, the granulation tank may, as needed, have auxiliary stirring blades positioned to rotate about an axis different from the main stirring blades. These auxiliary stirring blades can be positioned, for example, on the side of the granulation tank without interfering with the main stirring blades. Hereinafter, examples of granulation tanks equipped with these stirring blades are shown, and preferred examples of methods for manufacturing composite particles are specifically described.
[0116] Figure 1This is a schematic plan view of a granulation tank 10 used in a method for manufacturing composite particles according to one embodiment of the present invention. Furthermore, Figure 2 This is a schematic cross-sectional view of a granulation tank 10 used in a method for manufacturing composite particles according to one embodiment of the present invention. Figure 2 Equivalent to in Figure 1 A cross-sectional view of the granulation tank 10 cut along the dashed line II-II. (See figure) Figure 1 As shown, the granulation tank 10 includes a container 100 and a rotating shaft A. 200 The main stirring blades 200 are arranged to rotate around the center. Furthermore, the granulation tank 10 can also be equipped with a mechanism that allows it to rotate with the rotating shaft A, as needed. 200 Non-parallel axis of rotation A 300 The auxiliary stirring blades 300 are arranged to rotate around the center.
[0117] Container 100 is configured to contain positive electrode active material, carbon-based conductive material, binder resin, and solvent, and their mixing is performed within container 100. For example, container 100 may be cylindrical with a circular bottom 110 and top 120, or it may be tapered along a portion of its height. For example, it may be tapered along a continuous portion 130 from the top 120. Container 100 is typically configured such that its bottom 110 is parallel to the horizontal direction. Container 100 may include a supply port (not shown) for supplying raw materials such as positive electrode active material into container 100, and an outlet (not shown) for removing composite particles from container 100.
[0118] The main stirring blades 200 are typically located at the bottom 110 of the container 100. From the viewpoint of achieving uniform mixing, the rotation axis A of the main stirring blades 200... 200 Preferably, it is positioned at the center of the bottom 110. When the container 100 has a cylindrical shape, the rotation axis A of the main stirring blade 200... 200 It can be aligned with the central axis of the cylindrical shape of container 100. In this embodiment, a rotation axis A, which is parallel to the vertical direction, is shown at the center of the bottom 110 of container 100. 200An example of a main stirring blade 200 arranged in a centrally rotating manner will be described. Furthermore, the main stirring blade 200 typically has one or more main blades 210. The number and shape of these main blades 210 are not particularly limited; in this embodiment, a main stirring blade 200 with three main blades 210 is shown as an example. Moreover, generally, in the drive section 220 of the main stirring blade 200, a venting mechanism (not shown) for introducing a sealing gas into the container 100 is provided to prevent powder (positive electrode active material, carbon-based conductive material, composite particles, etc.) from entering the drive section 220. As the sealing gas, an inert gas is preferred, and nitrogen, for example, can be used.
[0119] The auxiliary stirring blade 300 is capable of rotating along the same axis A as the main stirring blade 200. 200 Non-parallel axis of rotation A 300 The rotation is centered on a pivot point. The rotation axis A of the main stirring blade 200 is... 200 Rotation axis A of auxiliary stirring blade 300 300 The angle θ formed is typically 20° or more, preferably 30° or more, more preferably 45° or more, and typically 90° or less. For example, the rotation axis A of the main stirring blade 200 200 Rotation axis A of auxiliary stirring blade 300 300 It can also be vertical. Typically, the auxiliary stirring blades 300 are disposed on the side 140 of the container 100. In this embodiment, a rotation axis A, parallel to the horizontal direction, is shown on the side 140 of the container 100. 300 An example of a secondary stirring blade 300 arranged in a rotating manner around a center is described. Furthermore, the secondary stirring blade 300 typically has one or more secondary blades 310. The number and shape of these secondary blades 310 are not particularly limited; in this embodiment, an example of a secondary stirring blade 300 having anchor-shaped blades as secondary blades 310 is shown. Furthermore, generally, similar to the drive section 220 of the main stirring blade 200, a venting mechanism (not shown) for introducing a sealing gas into the container 100 is provided in the drive section 320 of the secondary stirring blade 300 to prevent powder from impregnating the drive section 320. As the sealing gas, an inert gas is preferred; for example, nitrogen can be used.
[0120] Furthermore, the granulation tank 10 preferably includes a supply device for supplying the liquid composition. As this supply device, a nozzle 400 (in which the liquid composition is sprayed in a mist-like manner) is preferably preferred. Figure 1(Illustrations omitted). A dual-fluid spray nozzle can also be used as the spray nozzle 400, which sprays atomizing gas from around the nozzle 400. The flow of this atomizing gas pulverizes and atomizes the liquid composition, resulting in a mist. An inert gas is preferred as the atomizing gas; for example, nitrogen can be used. The number of spray nozzles 400 can be one or more. The spray nozzles 400 can be located at the top 120 or the side 140 of the container 100.
[0121] Commercially available products can be used as the pelletizing tank 10 described above. Examples of commercially available pelletizing tanks 10 include the "High-Speed Mixer" manufactured by Earth Technica, the "FM Mixer" manufactured by NIPPON COKE, the "Vertical Granulator" manufactured by Powrex, the "CF Granulator" manufactured by Freund Sangyo, the "High-Speed Mixing Granulator" manufactured by Nara Machine Works, the "SP Granulator" manufactured by DALTON, and the "BALANCE GRAN" manufactured by Freund Sangyo.
[0122] The method for manufacturing composite particles using the example of granulation tank 10 includes step (i) of stirring a positive electrode active material within the granulation tank 10 to achieve a stirred state. Specifically, the positive electrode active material is supplied to the container 100 of the granulation tank 10, forming a powder layer (not shown) containing the positive electrode active material within the container 100. Then, the main stirring blade 200 is rotated to stir the positive electrode active material. At this time, if necessary, not only the main stirring blade 200 but also the auxiliary stirring blade 300 can be rotated for stirring. The particles of the positive electrode active material that become the raw material may agglomerate, and this agglomeration can be broken up by stirring in step (i). Furthermore, the positive electrode active material that becomes the raw material may contain liquid components such as moisture that adhered during manufacturing and storage. By stirring in step (i), the amount of the aforementioned liquid components can be reduced, and preferably, they can be removed.
[0123] During the stirring process in step (i), the linear velocity of the main stirring blade 200 and the auxiliary stirring blade 300 is preferably 1 m / s or more and 20 m / s or less.
[0124] During stirring, a sealing gas is introduced into the container 100 from the drive section 220 of the main stirring blade 200 and the drive section 320 of the auxiliary stirring blade 300. The flow rate (ventilation volume) of this sealing gas is preferably set such that the ratio of the flow rate of the sealing gas flowing into the container 100 of the granulation tank 10 to the capacity of the container 100 (flow rate / capacity) is 0.1 / min or more and 1000 / min or less. Furthermore, in one example, the temperature of the sealing gas is preferably less than 50°C, more preferably less than 45°C, further preferably less than 40°C, particularly preferably less than 30°C, and preferably more than 5°C, more preferably more than 10°C, and even more preferably more than 15°C.
[0125] There is no particular limitation on the mixing time (pre-mixing time) in step (i), for example, it can be more than 5 minutes and less than 60 minutes.
[0126] The method for manufacturing composite particles using the example of granulation tank 10 includes, after step (i) above, a step (ii) of spraying a liquid composition comprising a carbon-based conductive material, a binder resin, and a solvent onto a stirred positive electrode active material. In step (ii), since the liquid composition is sprayed onto the positive electrode active material, the powder layer within container 100 becomes a state containing not only the positive electrode active material but also the carbon-based conductive material and the binder resin. As a result, the positive electrode active material, the carbon-based conductive material, and the binder resin agglomerate, gradually forming composite particles. Furthermore, in step (ii), the powder layer is stirred by rotating the main stirring blade 200. Alternatively, if necessary, not only the main stirring blade 200 but also the auxiliary stirring blade 300 can be rotated for stirring. Since the liquid composition is sprayed while continuously stirring, collisions between particles and between particles and the solvent occur simultaneously with the formation of the composite particles in the powder layer, resulting in the granulation of the composite particles. Therefore, in step (ii), the formation and granulation of composite particles are carried out simultaneously in the presence of a solvent, and the aforementioned composite particles can be obtained.
[0127] Preferred step (ii) The relative vapor pressure P of the solvent in the granulation tank 10 (i.e., in the container 100) R The experiment was conducted under specific conditions. Based on the inventors' research, the carbon atom dispersion s of the manufactured composite particles was determined. 2 The degree of humidity in the diffusion granulation environment during step (ii) has a significant impact. Furthermore, the aforementioned degree of humidity is highly dependent on the relative vapor pressure P of the solvent in the diffusion granulation environment during step (ii). R Related. Specifically, relative vapor pressure P RThe larger the value, the more solvent is supplied to the granulation tank 10 and becomes a liquid phase, thus indicating that the environment inside the granulation tank 10 is humid. Therefore, by appropriately setting the relative vapor pressure P of the solvent inside the granulation tank 10... R It can smoothly produce carbon atom dispersion s 2 The composite particles are within the aforementioned range. Specifically, the relative vapor pressure P of the solvent in the granulation tank 10 in step (ii) is... R The range is preferably 0.10 or more, more preferably 0.11 or more, even more preferably 0.15 or more, and preferably 0.9 or less, more preferably 0.8 or less. Therefore, the relative vapor pressure P R The range can be, for example, a range of 0.10 or higher and 0.9 or lower, a range of 0.10 or higher and 0.8 or lower, a range of 0.11 or higher and 0.9 or lower, a range of 0.11 or higher and 0.8 or lower, a range of 0.15 or higher and 0.9 or lower, or a range of 0.15 or higher and 0.8 or lower.
[0128] The relative vapor pressure P of the solvent in granulation tank 10 R By P R =P m / P0 indicates that, here, "P" means "P". m "P" represents the pressure of the solvent vapor within the granulation tank 10, assuming that all the solvent supplied to the granulation tank 10 vaporizes into solvent vapor. Hereinafter, the pressure P mentioned above will sometimes be referred to as "solvent vapor". m The term "proposed pressure of solvent vapor" P m In addition, "P0" represents the saturated vapor pressure of the solvent at the temperature inside the granulation tank 10.
[0129] Estimated pressure P of solvent vapor m [kPa] can be measured by the following method. Measure the flow rate [g / min] of the solvent in the liquid composition supplied to the granulation tank 10. Assuming that the solvent is completely vaporized in the granulation tank 10, convert its flow rate to a volumetric quantity V. m [L / min]. This conversion can typically be performed using the pressure P and temperature T within the granulation tank 10, through the ideal gas law. Then, the solvent concentration C in the total flow rate of the gas supplied to the granulation tank 10 is calculated on a volume basis. m For example, when supplying a flow rate V to the granulation tank 10... s Sealing gas and flow rate V a In the case of atomized gas, the above concentration C m Able to pass through "C" m =V m / (V m +V s +V aThe calculation is performed using the formula ")". Then, the pressure P and concentration C within the granulation tank 10 are compared. m Multiplying them together allows us to obtain the estimated pressure P of the solvent vapor. m .
[0130] On the other hand, the saturated vapor pressure of the solvent at temperature T within the granulation tank 10 can be calculated using the Antoni formula based on the temperature within the granulation tank 10. In the above measurements, the pressure P within the granulation tank 10 is typically atmospheric pressure, and can be, for example, 1 atm. Furthermore, the temperature T within the granulation tank 10 can be the temperature of the powder layer being stirred within the granulation tank 10 (the temperature of the powder layer is typically consistent with the temperature of the positive electrode active material).
[0131] The relative vapor pressure P of the solvent in granulation tank 10 R The measurement can also be performed using the methods described in the embodiments described later.
[0132] In the granulation tank 10, with the spray nozzle 400 positioned at the top 120, a liquid composition is typically sprayed onto the positive electrode active material located vertically downwards. In this case, a relative vapor pressure P exists. R The higher the relative vapor pressure P, the greater the tendency for the manufactured composite particles to have higher particle strength. Therefore, from the viewpoint of improving particle strength, a relative vapor pressure P is preferred. R High. Specifically, with the spray nozzle 400 positioned at the top 120, the relative vapor pressure P R The range is preferably 0.5 or more, more preferably 0.6 or more, and even more preferably 0.7 or more.
[0133] In the granulation tank 10, with the spray nozzle 400 positioned on the side 140, a liquid composition is typically sprayed onto the positive electrode active material located laterally in the horizontal direction. In this case, a relative vapor pressure P exists. R The lower the relative vapor pressure P, the higher the particle strength of the manufactured composite particles tends to be. Therefore, from the viewpoint of improving particle strength, a relative vapor pressure P is preferred. R Low. Specifically, with the spray nozzle 400 positioned on the side 140, the relative vapor pressure P is low. R The range is preferably less than 0.3, and more preferably less than 0.2.
[0134] Specifically, relative vapor pressure P R The spray rate of the liquid composition from the spray nozzle 400 [g / min], the flow rate of the atomizing gas [L / min], the flow rate of the sealing gas [L / min], and the temperature within the granulation tank 10 can be adjusted. Unless otherwise specified, the spray rate of the liquid composition refers to the amount of liquid composition sprayed from the spray nozzle 400 per unit time.
[0135] The ratio of the injection velocity [g / min] of the liquid composition ejected from the spray nozzle 400 to the flow rate [L / min] of the atomizing gas (liquid composition injection velocity / atomizing gas flow rate) is preferably 0.2 g / L or more, more preferably 0.4 g / L or more, even more preferably 0.6 g / L or more, and preferably 3.0 g / L or less, more preferably 2.0 g / L or less, even more preferably 1.5 g / L or less. The above ratio is related to the droplet size of the liquid composition ejected from the spray nozzle 400. When the above ratio is within the above range, the particle strength of the composite particles can be enhanced. Furthermore, it is generally possible to smoothly manufacture particles with the above-mentioned dispersity s. 2 Composite particles.
[0136] The temperature within the granulation tank 10 can be set within a range capable of producing the aforementioned composite particles. In one example, the temperature range within the granulation tank 10 is preferably 0°C or higher, more preferably 10°C or higher, even more preferably 20°C or higher, and preferably 100°C or lower, more preferably 80°C or lower, and even more preferably 60°C or lower. As described above, the temperature within the granulation tank 10 can be measured as the temperature of the powder layer being stirred within the granulation tank 10. Specifically, the temperature is preferably determined based on the composition of the liquid composition (such as a solvent), the injection rate, the flow rate of the atomizing gas, and the flow rate of the sealing gas, so that a relative vapor pressure P within the aforementioned range can be obtained. R Choose in this way.
[0137] As described above, a sealing gas and an atomizing gas are introduced into the granulation tank 10. The range of the flow rate of these gases into the granulation tank 10 divided by the capacity of the granulation tank 10 (flow rate / capacity) is preferably 0.1 / min or more and 1000 / min. The specific value (flow rate / capacity) is preferably based on the injection rate of the liquid composition ejected from the spray nozzle 400 and the temperature within the granulation tank 10, so that a relative vapor pressure P within the above-mentioned range can be obtained. R Choose in this way.
[0138] The linear velocity range of the stirring blades, such as the main stirring blade 200 and the auxiliary stirring blade 300, can be set within the range of the composite particles that can be manufactured. In one example, from the viewpoint of controlling the particle size of the composite particles within an appropriate range, it is preferable that the linear velocity range of the stirring blades, such as the main stirring blade 200 and the auxiliary stirring blade 300, is 1 m / s or more and 20 m / s or less.
[0139] In step (ii), the spraying of the liquid composition from the spray nozzle 400 can be performed intermittently, but is preferably performed continuously. The spraying time of the liquid composition can be set within a range that enables the production of the aforementioned composite particles. In one example, the spraying time can be more than 5 minutes and less than 60 minutes.
[0140] The method for manufacturing composite particles using the example of granulation tank 10 may further include any steps combined with steps (i) and (ii). The method for manufacturing composite particles may include, for example, a step of stirring the composite particles and granulating them after step (ii). Furthermore, the method for manufacturing composite particles may include, for example, a step of stirring the positive electrode active material using a stirring device different from that used in granulation tank 10 before step (i).
[0141] Positive electrode for electrochemical components
[0142] The aforementioned composite particles can be used to manufacture positive electrodes for electrochemical devices. This positive electrode typically includes a current collector and a positive electrode composite material layer formed on the current collector, the positive electrode composite material layer comprising the composite particles.
[0143] As the material for the current collector, materials with both electrical conductivity and electrochemical durability are preferred. Specific examples of current collector materials include metals, carbon, and conductive polymers, with metals being preferred. Examples of metals include iron, copper, aluminum, gold, platinum, nickel, tantalum, titanium, stainless steel, and their alloys; among these, aluminum and aluminum alloys are preferred from the viewpoint of electrical conductivity and voltage resistance. When high voltage resistance is required, high-purity aluminum disclosed in Japanese Patent Application Publication No. 2001-176757 is preferred. A single current collector material can be used, or two or more materials can be used in combination.
[0144] Current collectors generally have a film-like or sheet-like shape. The thickness of the current collector can be appropriately selected according to the intended use, preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and preferably 200 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less.
[0145] A cathode composite material layer containing composite particles is formed on the current collector. This cathode composite material layer may also contain only composite particles. The amount of cathode composite material layer per unit area is not particularly limited; in one example, 1 mg / cm³ is preferred. 2 The above, more preferably 2 mg / cm³ 2 The above is further preferred to be 5 mg / cm³. 2 The above, and preferably 100 mg / cm³ 2 The following is more preferably 50 mg / cm³ 2 The following is a further preferred value: 30 mg / cm³ 2 the following.
[0146] The positive electrode can be manufactured, for example, by pressing composite particles onto a current collector. Preferably, the positive electrode can be manufactured by a manufacturing method that includes forming a composite particle layer on a current collector and pressing the composite particle layer. For example, the composite particles can also be fed to a roller press and rolled onto a current collector, thereby pressing the composite particles onto the current collector to form a positive electrode composite material layer. The temperature and pressure conditions during pressing can be appropriately set according to the target positive electrode density.
[0147] <Electrochemical Components>
[0148] By using the aforementioned positive electrode, an electrochemical element can be obtained. This electrochemical element includes the aforementioned positive electrode. Examples of electrochemical elements include lithium-ion secondary batteries, electric double-layer capacitors, and lithium-ion capacitors, with lithium-ion secondary batteries being preferred.
[0149] The following description uses a lithium-ion secondary battery as an example of an electrochemical element. A lithium-ion secondary battery includes the aforementioned positive electrode, negative electrode, and electrolyte. Furthermore, lithium-ion secondary batteries typically also include a separator.
[0150] There are no particular limitations on the negative electrode; any known negative electrode can be used. Typically, the negative electrode comprises a current collector for negative electrodes and a negative electrode composite material layer containing negative electrode active material.
[0151] As an electrolyte, an organic electrolyte in which the supporting electrolyte is dissolved in an organic solvent is typically used. As a supporting electrolyte, for example in lithium-ion secondary batteries, lithium salts can be used. Examples of lithium salts include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, and (C2F5SO2)NLi. Among these, LiPF6, LiClO4, and CF3SO3Li are preferred due to their high solubility in solvents and high degree of dissociation. One electrolyte can be used alone, or two or more can be used in combination.
[0152] As the organic solvent for the electrolyte, solvents capable of dissolving and supporting the electrolyte can be used. For example, preferred organic solvents for lithium-ion secondary battery electrolytes include carbonate solvents such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butyl carbonate (BC), methyl ethyl carbonate (EMC), and vinylene carbonate (VC); ester solvents such as γ-butyrolactone and methyl formate; ether solvents such as 1,2-dimethoxyethane and tetrahydrofuran; and sulfur-containing compound solvents such as sulfolane and dimethyl sulfoxide. These solvents can be used alone or in combination of two or more. The concentration of the electrolyte in the electrolyte can be appropriately adjusted. Furthermore, the electrolyte can contain any additives.
[0153] There are no particular limitations on the separator membrane. For example, a separator membrane having a microporous membrane formed of a polyolefin resin (e.g., polyethylene, polypropylene, polybutene, polyvinyl chloride) as the separator membrane substrate can also be used. Furthermore, as a separator membrane, a separator membrane with functional layers (porous membrane layer or adhesive layer) provided on one or both sides of the separator membrane substrate can also be used.
[0154] Lithium-ion secondary batteries can be manufactured by, for example, overlapping the positive and negative electrodes with a separator, winding or folding them according to the battery shape as needed, placing them in a battery container, injecting electrolyte into the battery container, and sealing it. To suppress internal pressure rise and overcharging / discharging, overcurrent protection components such as fuses and PTC elements, porous metal mesh, and conductive plates can be added as needed. The shape of the secondary battery can be any of the following: coin-shaped, button-shaped, sheet-shaped, cylindrical, square, or flat.
[0155] Example
[0156] The present invention will now be specifically described based on embodiments, but the present invention is not limited to these embodiments. In the following description, unless otherwise specified, "%" and "parts" refer to quantities based on mass. Furthermore, unless otherwise specified, the operations described below are performed under normal temperature and pressure (23°C, 1 atm).
[0157] <Measurement and Evaluation Methods>
[0158] (Experiment 1. Dispersion of carbon atoms s in composite particles) 2 (Measurement method)
[0159] The composite particles were photographed at 2000x magnification using a SEM (Scanning Electron Microscope; JEOL Ltd. "FE-SEM7800F") to obtain a surface observation image (1280 pixels × 1024 pixels). This surface observation image was divided into small square images of 100 pixels x 100 pixels. From the obtained multiple small square images, the small square images containing blank areas where no composite particles were found were removed, and the remaining n small square images were used as the measurement objects. In any of the embodiments and comparative examples described later, n is in the range of 80 or more and 120 or less.
[0160] In the captured surface observation images, the positive electrode active material appears white, carbon atoms (including carbon atoms from carbon black and carbon atoms from the binder resin) appear light gray, and the voids where they are absent appear dark gray or black. Therefore, the area ratio of carbon atoms, represented by light gray, was measured in each small area image.
[0161] The area ratio of carbon atoms was measured using the image processing software "OpenCV" (https: / / opencv.org / ) in the following manner.
[0162] The surface observation image is processed into three regions: a region representing the positive electrode active material (white), a region representing carbon atoms (light gray), and a region representing voids (dark gray or black). In the surface observation image, the regions representing the positive electrode active material, carbon atoms, and voids can be clearly distinguished visually based on differences in brightness. Therefore, in the aforementioned three-dimensionalization process, a brightness threshold is set to distinguish the regions representing the positive electrode active material from the carbon atom regions while carefully visually verifying the difference. Similarly, a brightness threshold is set to distinguish the regions representing carbon atoms from the void regions while carefully visually verifying the difference. Then, using these thresholds, pixel-based brightness three-dimensionalization is performed to separate the regions representing the positive electrode active material, carbon atoms, and voids.
[0163] In each small region image after ternary processing in this manner, the area ratio of carbon atoms is determined. Specifically, in the small region image, binarization processing is performed to distinguish the carbon atom portion from the positive electrode active material portion and the void portion. Then, the area ratio of carbon atoms is determined by the ratio of the number of pixels contained in the carbon atom portion to 100% of the total number of pixels contained in the small region image. Hereinafter, the area ratio of carbon atoms in the i-th small region image is sometimes expressed as "x". i “i” represents an integer from 1 to n.
[0164] Calculate the average area ratio of carbon atoms in n small regions of an image. aThen, the area ratio x of carbon atoms in all n small regions of the image. i With average x a The square of the difference (x) i -x a ) 2 Summing is performed, and the sum is divided by the number of small-area images, n, to calculate the dispersion s of carbon atoms in the composite particles. 2 Specifically, the dispersion s is calculated based on the following equation (1). 2 .
[0165]
[0166] (Experiment 2. Method for measuring the particle strength of composite particles)
[0167] A laser diffraction particle size distribution measurement device (Microtrac MT-3000II) was prepared. This device disperses sample particles using compressed air and measures the particle size distribution of the dispersed particles using laser diffraction. Using this device, the particle size distribution of the composite particles was measured on a volume basis, and the particle size at which the cumulative volume reaches 50% from the smallest diameter side was defined as the D50 particle size "D50". The measurements were performed at dispersion pressures (compressed air pressures) of 0.1 MPa and 0.25 MPa. The ratio "D50(0.25MPa) / D50(0.1MPa)" of the D50 particle size measured at 0.25 MPa and the D50 particle size measured at 0.1 MPa was obtained as the particle strength. The greater the particle strength, the higher the mechanical strength of the composite particles.
[0168] (Experiment 3. Measurement method of powder resistivity of composite particles)
[0169] The probe unit (3.1 cm²) of the powder resistance measurement system (Mitsubishi Chemical Analytech "MCP-PD51") 2 4.0g of composite particles were added to the powder, and the powder resistance was measured when a pressure of 20kN was applied.
[0170] (relative vapor pressure P) R (Measurement method)
[0171] In the embodiments and comparative examples described later, the relative vapor pressure in the granulation tank was measured by the following method.
[0172] The flow rate [g / min] of the solvent (cyclohexane) in the liquid composition injected into the positive electrode active material is measured. Assuming the solvent is completely vaporized in the granulation tank, this flow rate is converted to a volumetric basis [L / min]. Specifically, the solvent flow rate is converted to a mass basis [mol / min]. Using the pressure and temperature within the granulation tank, the volumetric flow rate V of the solvent is calculated using the ideal gas law. m [L / min].
[0173] The solvent flow rate V obtained in this manner m The solvent concentration relative to the total gas supplied to the granulation tank is calculated on a volume basis. In the examples and comparative examples described later, in the granulation tank, atomizing gas (nitrogen) is sprayed around the nozzle to spray the liquid composition. Furthermore, to prevent raw materials from mixing into the drive sections of the main and auxiliary stirring blades, sealing gas (nitrogen) is introduced into each drive section. Thus, the flow rate of the total gas supplied to the granulation tank is determined by the solvent flow rate V. m [L / min], flow rate of atomizing gas V a [L / min] and the flow rate V of the sealing gas s The total [L / min] is expressed as the sum. Therefore, the solvent flow rate V m Divide by the total flow rate of gas supplied to the granulation tank (V) m [L / min]+V a [L / min]+V s [L / min]), calculate the solvent concentration C. m Then, the concentration C of the solvent is determined. m Multiply by the pressure P inside the granulation tank to calculate the pressure of the solvent vapor (estimated pressure of the solvent vapor) P inside the granulation tank, assuming that all the supplied solvent is vaporized into solvent vapor. m [kPa].
[0174] On the other hand, the temperature inside the granulation tank is substituted into the Antoni formula to calculate the saturated vapor pressure P0 [kPa] of the solvent at the temperature inside the granulation tank. The coefficients in the Antoni formula are those described in the Chemical Engineering Handbook (edited by the Chemical Engineering Society, revised 5th edition, Maruzen, 2004, page II-182). The estimated pressure P of the solvent vapor is then used. m Dividing [kPa] by the saturated vapor pressure P0[kPa] yields the relative vapor pressure P of the solvent in the granulation tank. R =P m / P0.
[0175] <Manufacturing Example 1. Manufacturing of Adhesive Resin A1>
[0176] In a reactor equipped with a stirrer and thoroughly nitrogen-purged, 270 parts of dehydrated cyclohexane and 0.53 parts of ethylene glycol dibutyl ether were added, followed by 0.47 parts of n-butyllithium (15% cyclohexane solution). While stirring the entire mixture at 60°C, 12.5 parts of dehydrated styrene were continuously added to the reactor over 40 minutes. After the addition was complete, the mixture was stirred at 60°C for another 20 minutes. Gas chromatography analysis showed a polymerization conversion of 99.5% at this point. Next, 75.0 parts of dehydrated isoprene were continuously added to the reaction mixture over 100 minutes, followed by stirring for another 20 minutes. The polymerization conversion at this point was 99.5%. Subsequently, another 12.5 parts of dehydrated styrene were continuously added over 60 minutes, followed by stirring for another 30 minutes. The polymerization conversion at this point was approximately 100%. Here, 0.5 parts of isopropanol were added to the reaction solution to terminate the reaction. Of the structural units derived from all isoprene in the obtained block copolymer, 58% were derived from 1,2- and 3,4-addition polymerization. Next, the polymer solution was transferred to a pressure reactor equipped with a stirrer, and 7.0 parts of a diatomaceous earth-supported nickel catalyst (manufactured by Nichibukai Chemical Co., Ltd., product name "E22U", nickel loading 60%) and 80 parts of dehydrated cyclohexane were added and mixed. The reactor was purged with hydrogen, and hydrogen was supplied while the solution was stirred, and the hydrogenation reaction was carried out at 190°C and 4.5 MPa for 6 hours. After the hydrogenation reaction was completed, the reaction solution was filtered to remove the hydrogenation catalyst. Then, 1.0 part of a xylene solution containing 0.1 part of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (manufactured by KOYO Chemical Research Institute Co., Ltd., product name "Songnox1010") as a phenolic antioxidant was added to the filtrate and dissolved. Cyclohexane was then added to prepare a solution of the bonding resin A1.
[0177] <Manufacturing Example 2. Manufacturing of Liquid Composition>
[0178] A liquid composition (solid content concentration 5 wt%, viscosity 300 mPa·s) was prepared by mixing 6.3 parts by weight of the bonding resin A1 obtained by drying the solution prepared in Manufacturing Example 1, 18.0 parts by weight of carbon black as a conductive additive, and 461.7 parts by weight of cyclohexane as a solvent. The D50 particle size of the carbon black in the liquid composition was measured and found to be 0.1 μm.
[0179] <Example 1>
[0180] A composite particle making apparatus I (large capacity type) is prepared as a granulation tank. This granulation tank includes a cylindrical container (400 mm inner diameter, 25 L capacity) with its axial direction perpendicular to the vertical direction; a main stirring blade positioned at the center of the bottom of the cylindrical container, capable of rotating around a vertical axis; and auxiliary stirring blades positioned on the side of the cylindrical container, capable of rotating around a horizontal axis. The main stirring blade is an inclined paddle blade with three 390 mm diameter main blades. Furthermore, the auxiliary stirring blades have V-shaped anchor blades with a diameter of 100 mm. To prevent raw materials from mixing into the drive sections of the main and auxiliary stirring blades, a sealing mechanism is provided in each drive section by introducing a sealing gas (nitrogen). Using the composite particle making apparatus I as the granulation tank, composite particles are manufactured by performing (i) a pre-stirring operation and (ii) a composite particle forming operation in this sequence.
[0181] As part of (i) the pre-stirring operation, 97.0 parts by weight (11215 g) of NMC631 (LiNi) as a positive electrode active material for lithium-ion batteries was added to the granulation tank. 0.6 Mn 0.3 Co 0.1 O2 (D50 particle size 4μm). While introducing room temperature (25℃) sealed gas into the granulation tank at a flow rate of 170 L / min, the main and auxiliary stirring blades rotate to stir the positive electrode active material. The linear velocity of the main stirring blade is 4.0 m / s (196 rpm), and the linear velocity of the auxiliary stirring blade is 15.7 m / s (3000 rpm).
[0182] Next, as part of the composite particle formation operation (ii), while stirring the positive electrode active material as described above, 3.0 parts by weight (6937 g of liquid composition) of the liquid composition manufactured in Manufacturing Example 2, calculated based on solid components, were sprayed onto the positive electrode active material at a spraying rate of 300 g / min for approximately 20 minutes. The liquid composition was sprayed from a two-fluid spray nozzle (top nozzle) located at the top of the cylindrical container. At this time, the flow rate of the atomizing gas (nitrogen) sprayed from around the nozzle for spraying the liquid composition was 300 L / min. By spraying the liquid composition, a powder layer consisting of a raw material composition containing the positive electrode active material and the solid components of the liquid composition (conductive material and binder resin A1) was formed in the granulation tank. Composite particles were formed by stirring this powder layer. The temperature of the powder layer in step (ii) was measured using a thermocouple and the result was 35.0°C.
[0183] The composite particles manufactured by performing the above operations (i) to (ii) in this order are evaluated by the above method.
[0184] <Example 2>
[0185] A composite particle making apparatus II (small capacity type) is prepared as a granulation tank. This granulation tank includes a cylindrical container (180 mm inner diameter, 1.5 L capacity) positioned perpendicular to the axial direction of the cylindrical container; a main stirring blade rotatable around a vertical axis at the center of the bottom of the cylindrical container; and auxiliary stirring blades rotatable around a horizontal axis on the side of the cylindrical container. The main stirring blade is an inclined paddle blade with three 170 mm diameter blades. The auxiliary stirring blades have V-shaped anchor blades with a 30 mm diameter. To prevent raw materials from mixing into the drive sections of the main and auxiliary stirring blades, each drive section is equipped with a sealing mechanism that uses a sealing gas (nitrogen) for sealing. Using the composite particle making apparatus II described above, composite particles are manufactured by performing (i) a pre-stirring operation and (ii) a composite particle forming operation in this sequence.
[0186] As part of (i) the pre-stirring operation, 97.0 parts by weight (873.0 g) of the same positive electrode active material as in Example 1 was added to the granulation tank. While introducing room temperature (25°C) sealed gas into the granulation tank at a flow rate of 200 L / min, the main stirring blades were rotated to stir the positive electrode active material. The linear velocity of the main stirring blades was 3.6 m / s (400 rpm). The auxiliary stirring blades were then stopped.
[0187] Next, as part of the composite particle formation operation (ii), while stirring the positive electrode active material as described above, 3.0 parts by weight (540 g of liquid composition) of the liquid composition prepared in Manufacturing Example 2, converted from solid components, were sprayed onto the positive electrode active material at a spraying rate of 25 g / min for approximately 22 minutes. The liquid composition was sprayed from a two-fluid spray nozzle (side nozzle) located on the side (horizontal end) of the cylindrical container. At this time, the flow rate of the atomizing gas (nitrogen) sprayed from around the nozzle for spraying the liquid composition was 25 L / min. By spraying the liquid composition, a powder layer consisting of a raw material composition containing the positive electrode active material and the solid components of the liquid composition (conductive material and binder resin A1) was formed in the granulation tank. Composite particles were formed by stirring this powder layer. The temperature of the powder layer in step (ii) was measured using a thermocouple and the result was 21.0 °C.
[0188] The composite particles manufactured by performing the above operations (i) to (ii) in this order are evaluated by the above method.
[0189] <Example 3>
[0190] The temperature of the powder layer in step (ii) was changed to 32.0°C. Otherwise, the composite particles were manufactured and evaluated using the same method as in Example 2. The temperature of the powder layer was changed by changing the temperature of the water (jacket water) introduced into the jacket covering the granulation tank (this was also done in the following examples and comparative examples).
[0191] <Example 4>
[0192] Except for the following, the composite particles were manufactured and evaluated using the same method as in Example 1.
[0193] • Change the linear velocity of the main stirring blades to 1.3 m / s (66 rpm).
[0194] • Stop the auxiliary stirring blades.
[0195] • Change the nozzle for spraying the liquid composition from a top nozzle to a two-fluid spray nozzle (side nozzle) located on the side (horizontal end) of a cylindrical container.
[0196] • Change the temperature of the powder layer in process (ii) to 72.0°C.
[0197] • The spraying speed of the liquid composition was changed to 150 g / min. As a result, the spraying of the liquid composition took approximately 42 minutes.
[0198] <Comparative Example 1>
[0199] Except for the following, the composite particles were manufactured and evaluated using the same method as in Example 2.
[0200] • Change the linear velocity of the main stirring blades to 4.1 m / s (460 rpm).
[0201] • Rotate the auxiliary stirring blades. The linear velocity of the auxiliary stirring blades is 4.7 m / s (3000 rpm).
[0202] • Change the nozzle for spraying the liquid composition from a side nozzle to a two-fluid spray nozzle (top nozzle) located at the top of a cylindrical container.
[0203] • Change the temperature of the powder layer in process (ii) to 24.9°C.
[0204] • Change the ventilation rate of the sealed gas to 10L / min.
[0205] <Comparative Example 2>
[0206] Except for the following, the composite particles were manufactured and evaluated using the same method as in Example 2.
[0207] • Change the linear velocity of the main stirring blades to 2.7 m / s (300 rpm).
[0208] • Rotate the auxiliary stirring blades. The linear velocity of the auxiliary stirring blades is 4.7 m / s (3000 rpm).
[0209] • Change the nozzle for spraying the liquid composition from a side nozzle to a two-fluid spray nozzle (top nozzle) located at the top of a cylindrical container.
[0210] • Change the temperature of the powder layer in process (ii) to 55.2°C.
[0211] • The spraying rate of the liquid composition was changed to 4 g / min. As a result, the spraying of the liquid composition took approximately 122 minutes.
[0212] • Change the ventilation rate of the sealed gas to 10L / min.
[0213] <Comparative Example 3>
[0214] Except for the following, the composite particles were manufactured and evaluated using the same method as in Example 2.
[0215] • The mass of the positive electrode active material added to the granulation tank is changed to 97.0 parts by weight (582g).
[0216] • The liquid composition of the positive electrode active material sprayed into a stirring state is converted into 3.0 parts by weight (the amount of the liquid composition is 360g) based on the solid component conversion.
[0217] • Change the temperature of the powder layer in process (ii) to 41.0℃.
[0218] • The spraying rate of the liquid composition was changed to 4 g / min. As a result, the spraying of the liquid composition took approximately 81 minutes.
[0219] <Results>
[0220] The results of the above-described embodiments and comparative examples are shown in the table below. Furthermore, the relationship between dispersity and powder resistivity in the results of the embodiments and comparative examples is shown in... Figure 3 The charts are shown below. The meanings of the abbreviations in the following tables are as follows.
[0221] Active material mass: The amount of positive electrode active material added to the granulation tank.
[0222] Slurry quantity: The amount of liquid composition sprayed into the granulation tank.
[0223] Tank temperature: The temperature inside the granulation tank in step (ii) of the compound particle formation operation.
[0224] Spraying speed: The spraying speed of the liquid composition sprayed onto the positive electrode active material.
[0225] "Top" spray position: Top nozzle located at the top of the cylindrical container.
[0226] Spray position "side": Side nozzles located on the side of a cylindrical container.
[0227] Saturated vapor pressure P0: The saturated vapor pressure of the solvent at the temperature inside the granulation tank.
[0228] Estimated pressure P m The estimated pressure of solvent vapor in the granulation tank.
[0229] Relative vapor pressure P R : The relative vapor pressure of the solvent in the granulation tank.
[0230] [Table 1]
[0231]
[0232] Explanation of reference numerals in the attached figures
[0233] 10: Granulation tank
[0234] 100: Container
[0235] 110: Bottom
[0236] 120: Top
[0237] 130: Part
[0238] 140: Side
[0239] 200: Main stirring blades
[0240] 210: Main blade
[0241] 220: Drive Unit
[0242] 300: Secondary stirring blades
[0243] 310: Sub-blade
[0244] 320: Drive Unit
[0245] 400: Spray nozzle
[0246] A 200 Rotation axis
[0247] A 300 Rotation axis
Claims
1. A composite particle for the positive electrode of an electrochemical device, comprising a positive electrode active material, a carbon-based conductive material, and a binding resin. The dispersion s of carbon atoms in the composite particles for the positive electrode of the electrochemical element, calculated by the following formula (1). 2 Between 0.5% and 1.0%, In equation (1), n represents the number of square images, which are obtained by segmenting a 1280-pixel × 1024-pixel surface observation image of the composite particles for the positive electrode of the electrochemical element obtained by taking a picture at 2000x magnification using a scanning electron microscope. The square image has a size of 100 pixels vertically × 100 pixels horizontally and does not include blank areas where the composite particles for the positive electrode of the electrochemical element were not photographed. n is 80 or higher and 120 or lower x i This indicates the area ratio of carbon atoms in each of the aforementioned images. x a This represents the average area ratio of carbon atoms in all the images described.
2. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, The composite particles used in the positive electrode of the electrochemical element have a particle strength of 0.6 or higher. The particle strength is expressed as the ratio of the D50 particle size "D50(0.25MPa)" measured under a pressure of 0.25MPa to the D50 particle size "D50(0.1MPa)" measured under a pressure of 0.1MPa, "D50(0.25MPa) / D50(0.1MPa)".
3. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, With a cross-sectional area of 3.1 cm 2 4.0g of the composite particles for the positive electrode of the electrochemical element were placed in a container, and the powder resistance of the composite particles for the positive electrode of the electrochemical element was measured to be less than 30Ω under a pressure of 20kN.
4. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, The content of the positive electrode active material is above 90% by weight and below 99.19% by weight.
5. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, The carbon-based conductive material contains more than 0.8% by weight and less than 5% by weight.
6. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, The content of the bonding resin is 0.01% by weight or more and 5% by weight or less.
7. The composite particles for the positive electrode of an electrochemical element according to claim 1, wherein, The D50 particle size of the carbon-based conductive material is 0.01 μm to 0.4 μm.
8. A method for manufacturing composite particles for the positive electrode of an electrochemical device, comprising the method of manufacturing composite particles for the positive electrode of an electrochemical device according to any one of claims 1 to 7, including: The positive electrode active material, carbon-based conductive material, binding resin and solvent are stirred and granulated.
9. The method for manufacturing composite particles for the positive electrode of an electrochemical element according to claim 8, wherein, include: Step (i) involves stirring the positive electrode active material in a granulation tank to obtain a stirred state. as well as Step (ii) involves spraying a liquid composition comprising the carbon-based conductive material, the binding resin, and the solvent onto the positive electrode active material in a stirred state.
10. The method for manufacturing composite particles for the positive electrode of an electrochemical element according to claim 9, wherein, The relative vapor pressure of the solvent in the granulation tank in step (ii) is 0.1 or higher and 0.9 or lower.
11. The method for manufacturing composite particles for the positive electrode of an electrochemical device according to claim 10, wherein, The step (ii) includes spraying the liquid composition from a nozzle disposed at the top of the granulation tank. The relative vapor pressure of the solvent in the granulation tank in step (ii) is 0.5 or higher.
12. The method for manufacturing composite particles for the positive electrode of an electrochemical element according to claim 10, wherein, The step (ii) includes spraying the liquid composition from a nozzle disposed on the side of the granulation tank. The relative vapor pressure of the solvent in the granulation tank in step (ii) is less than 0.
3.
13. A positive electrode for an electrochemical device, comprising a current collector and a positive electrode composite material layer formed on the current collector, The positive electrode composite material layer comprises composite particles for the positive electrode of an electrochemical element as described in any one of claims 1 to 7.
14. An electrochemical element having a positive electrode as described in claim 13.
Citation Information
Patent Citations
Electric double-layer capacitor
JP2001176757A
Method for manufacturing lithium ion secondary battery
JP2014078497A
Method for manufacturing lithium ion secondary battery
US20140079872A1